2013
DOI: 10.1111/jora.12072
|View full text |Cite
|
Sign up to set email alerts
|

Peer Networks and the Development of Illegal Political Behavior Among Adolescents

Abstract: This study examined to what extent peer influence explains the development of illegal political behavior controlling for peer selection, legal political peer influence, and gender effects. Late adolescents who filled out questionnaires at two annual measurements were used in a longitudinal social network approach (N = 1006; Mage = 16.62). Results showed that peers' involvement in illegal political behavior predicted adolescents' increases in illegal political behavior. Adolescents did not select other peers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…In the studies reported in this issue, researchers examined dynamics in networks and a range of behaviors, including externalizing problems, internalizing problems, substance use, healthcompromising behaviors, prosocial behavior, social goals, and happiness. Other topics recently investigated but not included in this issue are dynamics in networks and victimization (Sentse, Dijkstra, Salmivalli, & Cillessen, 2013;Sijtsema, Rambaran, & Ojanen, 2013), xenophobia (Van Zalk, Kerr, Van Zalk, & Stattin, 2013), political behaviors (Dahl & Van Zalk, 2014), and religious service attendance (Cheadle & Schwadek, 2012).…”
Section: Dynamics In Network and A Range Of Behaviorsmentioning
confidence: 99%
“…In the studies reported in this issue, researchers examined dynamics in networks and a range of behaviors, including externalizing problems, internalizing problems, substance use, healthcompromising behaviors, prosocial behavior, social goals, and happiness. Other topics recently investigated but not included in this issue are dynamics in networks and victimization (Sentse, Dijkstra, Salmivalli, & Cillessen, 2013;Sijtsema, Rambaran, & Ojanen, 2013), xenophobia (Van Zalk, Kerr, Van Zalk, & Stattin, 2013), political behaviors (Dahl & Van Zalk, 2014), and religious service attendance (Cheadle & Schwadek, 2012).…”
Section: Dynamics In Network and A Range Of Behaviorsmentioning
confidence: 99%
“…Early studies on socialization already made clear that children are never socialized merely by their family environment (Alwin, Cohen, and Manja Coopmans, Tanja van der Lippe & Marcel Lubbers 750 Newcomb 1991;Parsons and Bales 1956). Throughout adolescence and early adulthood, peersfriends at school in particularhave been found to influence a wide variety of attitudes and behaviours (Brechwald and Prinstein 2011;Dahl and Van Zalk 2014). One of the main mechanisms through which peer influence takes place is communication.…”
Section: War-specific Communication With Non-relativesmentioning
confidence: 99%
“…Numerous interactional processes and relationship factors have been shown to contribute to peer group influence on school misconduct and to deviant and illegal behavior more broadly (Dahl & van Zalk, 2013;Dishion & Dodge, 2005). Positive reinforcement of deviant behavior by close friends supports children's and adolescents' deviant behaviors based on observations of deviancy training (Dishion, Spracklen, Andrews, & Patterson, 1996;Snyder et al, 2008).…”
Section: School Misconduct and Peer Group Influencementioning
confidence: 99%